0
$\begingroup$

I stumbled upon the following exercise:

Find complex roots of a polynomial $x^2 - 5x + 7 - i$. The problem I have with this is not in the fact that I cannot solve it (I actually did), but I am searching for a more efficient or "smart" way of doing this.

The way I approached this problem was by writing x as a complex number ($x = a + bi$) and then substituted $x$ in the equation $x^2 - 5x + 7 - i = 0$. Then, after some rearranging I got two equations and solved the system for a and b. My result was correct, however, I am not satisfied because my method is rather tedious and I would like to hear from you, how to make this easier if possible.

Note: I have tried solving this as a quadratic equation the usual way, however, I stumbled upon $\sqrt{4i - 3}$ in the solution and I am not sure how to simplify this.

$\endgroup$
  • $\begingroup$ Stupid downvote. $\endgroup$ – Yves Daoust May 15 '18 at 9:40
0
$\begingroup$

Hint. Find $z=a+ib$ such that $z^2=\Delta=4i-3$: $$z^2=a^2-b^2+2iab=-3+4i\implies\begin{cases}a^2-b^2=-3\\ab=2\end{cases} \implies z=\pm(1+2i).$$ Now it should be easy to solve the quadratic equation $x^2 - 5x + 7 - i = 0$ in the "usual way".

$\endgroup$
0
$\begingroup$

I'll show you how to do $\sqrt{3-4i}$.

Let $(a+bi)^2 =c+di=z$

Then it can be derived that $$a=\pm\sqrt{\frac{c\pm|z|}{2}}, b=\pm\sqrt{\frac{-c\pm|z|}{2}}$$

For $z=-3+4i, |z|=\sqrt{3^2+4^2}=5$

Hence $$a=\pm\sqrt{\frac{3\pm5}{2}}=\pm i, \pm2$$ $$b=\pm\sqrt{\frac{-3\pm5}{2}}=\pm 1, \pm2i$$ Then you just need to play around with these (square them!) and find that $(1+2i)$ and $(-1-2i)$ are the square roots of $3-4i$

$\endgroup$
  • $\begingroup$ If you'd like me to explain how I got those formulae, just ask and I'll update my answer :) $\endgroup$ – Rhys Hughes May 15 '18 at 9:43
0
$\begingroup$

There is in fact no simpler way.

You can solve with the classical formulas and end up with the square root of a complex number. Then you can extract the square root using the polar form and the half-angle formulas*.

But this is not really simpler than the direct "plug $a+ib$" method that leads to a system of real quadratic equations in all cases.


*$$a+ib=\sqrt{a^2+b^2}(\cos\theta+i\sin\theta)$$ and

$$\sqrt{a+ib}=\sqrt[4]{a^2+b^2}\left(\cos\frac\theta2+i\sin\frac\theta2\right)\\ =\sqrt[4]{a^2+b^2}\left(\sqrt{\frac{1+\cos\theta}2}+i\sqrt{\frac{1-\cos\theta}2}\right)\\ =\sqrt[4]{a^2+b^2}\left(\sqrt{\frac{1+\dfrac a{\sqrt{a^2+b^2}}}2}+i\sqrt{\frac{1-\dfrac a{\sqrt{a^2+b^2}}}2}\right)\\ =\sqrt{\frac{\sqrt{a^2+b^2}+a}2}+i\sqrt{\frac{\sqrt{a^2+b^2}-a}2}.$$

$\endgroup$
0
$\begingroup$

Completing the square: $$x^2 - 5x + 7 - i=0 \iff \left(x-\frac52\right)^2=\frac{25}{4}-7+i \iff \\ x-\frac52=\pm\sqrt{-\frac34+i}=\pm (a+bi).$$ Note: $$(a+bi)^2=-\frac34+i \Rightarrow a^2-b^2+2abi=-\frac34+i \Rightarrow \\ \begin{cases}a^2-b^2=-\frac34\\ 2ab=1\end{cases}\Rightarrow (a,b)=\pm\left(\frac12,1\right).$$ Hence: $$x-\frac52=\pm\left(\pm\left(\frac12+i\right)\right)= \pm\left(\frac12+i\right)\Rightarrow\\ x_1=\frac52+\frac12+i=3+i;\\ x_2=\frac52-\frac12-i=2-i.$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.